RISE OF AUGMENTED REALITY IN GAMING TECHNOLOGY - Muhammad Fitri Azidi Bin Hisham’muddin; Muhammad Aliff Zikry Bin Saidon (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Augmented Reality (AR) has been a thing in the world today. This doesn’t leave the gaming industry untouched from AR technology from involving their self in this huge industry. The topic of this research is mainly to talk about how AR has rise recently in the gaming industry. The purpose of this research is to find out how AR has been involving in the gaming industry to this day. For this research, our method to do this research is  by reading and analysis the thesis and paperwork of previous research and also by involving in the conference manage by the company and industry that manage to implement AR in their game. The result that we got is quite interesting when the company that manage to pioneer in the AR for gaming, managed to monopoly the market of AR gaming considering that gaming industry is a big piece of pie and they manage to monopoly one of the genre. The implication of this research is that we can realize how there is a huge consumers were waiting for the AR gaming available to them. AR is quite interesting compare to Virtual Reality (VR) because we can concluding that VR is just like having a dream because it only bring us to their own room, compare to AR that implement and improving the reality into a more interesting world without us being lost to the real world.Keywords : augmented reality; virtual reality; game technology.